A memory-driven auditory program ensures selective and precise vocal imitation in zebra finches - Wan-chun Liu (Nature Portfolio, 2021)
Wan-Chun Liu et al. demonstrate that the sensory phase of vocal learning in zebra finches is split across two stages: (1) passive listening and formation of a memory, and (2) active listening and behavioral engagement of juveniles with adult tutors. Furthermore, they show that approach behavior is correlated with song imitation quality, and immediate early gene expression in the caudal medial nidopallium linked to auditory behavior.